Neutralization of bovine Concanavalin-A T cell supernatant-mediated anti-Cowdria ruminantium activity with antibodies specific to Interferon gamma but not to tumor necrosis factor - Mahan, S.M.; Sileghem, M.; Smith, G.E.; Byrom, B. (Wiley, 1996)
In an earlier study we demonstrated that Concanavalin‐A stimulated bovine T cell supernatants inhibited the growth of Cowdria ruminantium in bovine endothelial cells in vitro. An investigation was conducted to identify the cytokines which were responsible for this growth inhibition. Addition of antiserum against bovine interferon gamma (IFNγ) reproducibly neutralized the inhibitory effect of the T cell supernatants, whereas addition of antisera against bovine tumor necrosis factor alpha (TNFα) had no effect. The inhibitory effect of IFNγ on C. ruminantium growth was not mediated by the production of nitric oxide as there was no detectable difference in nitric oxide levels in cultures that were supplemented with T cell supernatants compared with those that were not. The IFNγ mediated anti‐C. ruminantium effect highlights the importance of cell mediated immune responses in control of these infections and in particular incriminates the protective role of T cells, or cells that secrete IFNγ.